THE IMPACT OF THE TRAVEL RESTRICTION POLICY ON THE PERCEPTIONS OF THE RISKS OF TRANSPORTATION BUSINESS ACTORS - Beni Ismarizal; Fitri Rahmafitria (Media Bina Ilmiah, 2023)
This study aims to analyze the impact of the PPKM policy on the tourism transportation industry and the movement of tourists to travel. Data collection was carried out using the in-depth interview method with 9 transportation industry players and 8 tourists interviewed within two months from November to December 2022. The technique for determining informants used purposive sampling. In this study using a qualitative descriptive analysis. The results obtained from this study prove that the PPKM policy greatly impacts the tourism transportation industry and the movement of tourists. So that until now we are faced with serious problems and become extraordinary challenges for tourism transportation industry players. This policy is also considered to be difficult for tourists who want to travel. Therefore, the results of these findings can be used as reference material for stakeholders, namely the government in formulating policies in the future. So that similar incidents become material considerations in implementing a public policy.